BANTUAN PEMBANGUNAN RUSUNAWA PADA LEMBAGA PENDIDIKAN TINGGI - Raflis Raflis (Jurnal Potensi, 2021)
With the issuance of Law Number 16 of 1985 concerning Flats, Draft General Guidelines for Compilation and Submission of Proposals for Development of Flats for Higher Education Number 1 of 2006 and Regulation of the State Minister of Public Housing Number 9/PERMEN/M/2008 concerning Guidelines for Assistance for Flats Development Simple rent (Rusunawa) at Higher Education Institutions and Boarding Education Institutions, so students can breathe a little easier to reduce the cost of education. The purpose of this study is to determine the effectiveness of the use of flats in universities.The research approach used in this research is a quantitative approach and a qualitative approach. Quantitative methods emphasize the existence of variables as objects of research and these variables must be defined in the form of the operationalization of each variable. This research is an ex facto research because it is carried out after all events have taken place.The results of this study indicate that so far the utilization of the building has not been optimal. This is because the building design does not match the habits of building users, even though the building design is a uniform design from the rusunawa construction aid provider. Moreover, other regions have different local wisdom according to the characteristics of each region.